2006
DOI: 10.1111/j.1468-1331.2006.01511.x
|View full text |Cite
|
Sign up to set email alerts
|

EFNS guidelines on pharmacological treatment of neuropathic pain

Abstract: Neuropathic pain treatment remains unsatisfactory despite a substantial increase in the number of trials. This EFNS Task Force aimed at evaluating the existing evidence about the pharmacological treatment of neuropathic pain. Studies were identified using first the Cochrane Database then Medline. Trials were classified according to the aetiological condition. All class I and II controlled trials (according to EFNS classification of evidence) were assessed, but lower-class studies were considered in conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
512
1
78

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 785 publications
(604 citation statements)
references
References 151 publications
(248 reference statements)
13
512
1
78
Order By: Relevance
“…Conversely the topical agent capsaicin is effective for PHN, but has been reported to have minimal effect for painful polyneuropathies (1,14). Our data challenge the relevance of using PHN as a model of neuropathic pain in pharmacological studies.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…Conversely the topical agent capsaicin is effective for PHN, but has been reported to have minimal effect for painful polyneuropathies (1,14). Our data challenge the relevance of using PHN as a model of neuropathic pain in pharmacological studies.…”
Section: Discussionmentioning
confidence: 58%
“…These analyses indicated that idiopathic trigeminal neuralgia was strongly associated with electric shocks only. From a therapeutic perspective, only trigeminal neuralgia responds particularly well to sodium channel blockers, including carbamazepine, oxcarbazepine and lamotrigine (1,25), which are more modestly effective for other neuropathic pain (1,5,36). Our data emphasize the relevance of distinct definitions, diagnostic and therapeutic algorithms for neuropathic pain and idiopathic trigeminal neuralgia (1, 35).…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations